UPAYA MENINGKATKAN PROFESIONALISME GURU BERLANDASKAN ILMU PENDIDIKAN DALAM MENCERDASKAN KEHIDUPAN BANGSA - Wahyu Sri Ambar Arum (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2007)
This article discusses the important roles of the teachers in educating people to have smart life. To enable the teachers to perform their tasks professionally, some requirements have to be fulfilled. The Indonesian government has already conducted a number of efforts to improve the teacher professionalism. However, some hindrances are still faced. Having analyzed the existing situation, the article suggests some ideas to improve the teacher professionalism.